Cryptotephras in the Lateglacial ICDP Dead Sea sediment record and their implications for chronology. (28th February 2021) - Neugebauer, Ina; Müller, Daniela; Schwab, Markus J.; Blockley, Simon; Lane, Christine S.; Wulf, Sabine; Appelt, Oona; Brauer, Achim
Abstract : Due to a lack of visible tephras in the Dead Sea record, this unique palaeoenvironmental archive is largely unconnected to the well‐established Mediterranean tephrostratigraphy. Here we present first results of the ongoing search for cryptotephras in the International Continental Drilling Program (ICDP) sediment core from the deep Dead Sea basin. This study focusses on the Lateglacial ( 15–11.4 cal. ka BP), when Lake Lisan – the precursor of the Dead Sea – shrank from its glacial highstand to the Holocene low levels. We developed a glass shard separation protocol and counting procedure that is adapted to the extreme salinity and sediment recycling of the Dead Sea. Cryptotephra is abundant in the Dead Sea record (up to 100 shards cm -3 ), but often glasses are physically and/or chemically altered. Six glass samples from five tephra horizons reveal a heterogeneous geochemical composition, with mainly rhyolitic and some trachytic glasses potentially sourced from Italian, Aegean and Anatolian volcanoes. Most shards likely originate from the eastern Anatolian volcanic province and can be correlated using major element analyses with tephra deposits from swarm eruptions of the Süphan Volcano 13 ka BP and with ashes from Nemrut Volcano, presumably the Lake Van V‐16 volcanic layer at 13.8 ka BP. In addition to glasses that match the TM‐10‐1 from Lago Grande di Monticchio (15 820±790 cal. a BP) tentatively correlated with the St. Angelo Tuff of Ischia, we further identified a cryptotephra with glass analyses which are chemically identical with those of the PhT1 tephra in the Philippon peat record (13.9–10.5 ka BP), and also a compositional match for the glass analyses of the Santorini Cape Riva Tephra (Y‐2 marine tephra, 22 024±642 cal. a BP). These first results demonstrate the great potential of cryptotephrochronology in the Dead Sea record for improving its chronology and connecting the Levantine region to the Mediterranean tephra framework.